Babesiosis in Cats: ABCD guidelines on prevention and management. Issue 7 (July 2013) - Hartmann, Katrin; Addie, Diane; Belák, Sándor; Boucraut-Baralon, Corine; Egberink, Herman; Frymus, Tadeusz; Gruffydd-Jones, Tim; Hosie, Margaret J; Lloret, Albert; Lutz, Hans; Marsilio, Fulvio; Möstl, Karin; et al.
Overview: Babesiosis is a tick-borne protozoan disease caused by parasites of the genus Babesia that belong to the Piroplasmida . The disease is named after the Romanian bacteriologist Victor Babeş. Babesiosis is also known as piroplasmosis (from Latin pirum, meaning 'pear', and plasma, 'image, formation'). Infection: Babesiosis affects domestic and wild animals and humans worldwide. While the disease is recognised in dogs around the world, it is found only rarely in cats. Human disease: Babesia species are common blood parasites of mammals. Human babesiosis is uncommon, but more cases in people have been reported recently, most likely because of rising awareness.